Aerobic fitness influences the response of maximal oxygen uptake and lactate threshold in acute hypobaric hypoxia. - Koistinen, P.; Takala, T.; Martikala, V.; Leppäluoto, J. (International Journal of Sports Medicine, 1995)
We studied 12 highly trained athletes, 6 male ice-hockey players and 6 cross-country skiers (2 females, 4 males). All of them participated in a maximal electrically braked bicycle ergometer test in a hypobaric chamber at the simulated altitude of 3000m (520 mmHg) and in normobaric conditions two days apart in random order. The maximal oxygen uptake was 57.4 +/- 7.1 (SD) ml/kg/min in normobaria (VO2maxnorm) and 46.6 +/- 4.9 (SD) ml/kg/min in hypobaric hypoxia (VO2maxhyp). The decrease in maximal oxygen uptake (delta VO2max) at the simulated altitude of 3000m correlated significantly (p 0.05, r = 0.61) to the maximal oxygen uptake in normobaric conditions (VO2maxnorm). The lactate threshold was 43.5 +/- 6.4 (SD) ml/kg/min in normobaria (VO2LTnorm) and 36.5 +/- 4.2 (SD) ml/kg/min in hypobaric hypoxia (VO2LThyp). The decrement (delta VO2LT) of lactate threshold in hypoxia correlated significantly (p 0.01, r = 0.68) with the lactate threshold in normobaric conditions (VOLTnorm). Thus we observed the largest reduction of both maximal oxygen uptake and lactate threshold during exercise at hypobaric hypoxia in the most fit athletes.